The causal effect of early marriage on women's bargaining power: Evidence from Bangladesh - Tauseef, Salauddin; Sufian, Farha Deba (Oxford University Press, 2024)
Early marriage restrains women's agency and bargaining strength in postmarital households, impairing their ability to make meaningful contributions to household decision making. This paper employs a comprehensive measure of women's empowerment in the domestic and productive spheres, and isolates the causal effect of age at marriage, instrumented by age at menarche, on their bargaining strength, using nationally representative data from Bangladesh. Results suggest that delayed marriages result in significantly higher empowerment scores and probability of being empowered for women, because of higher likelihood in achieving adequacy in their autonomy in agricultural production, control over income, ownership of assets and rights in those assets, and ability to speak in public. Favorable impacts of delayed marriage are also found on women's freedom of mobility, fertility choices, and their ability to decide on household expenses and investments, with the impacts likely coming via improvements in education and labor market outcomes when women married later.